Efek Nilai Hedonik Terhadap Cinta Merek: Efek Mediasi Emosi Konsumen dan Ikatan Merek Pada Pelanggan Reguler Makanan Siap Saji - Pandowo, Aditya (Jurnal Riset Manajemen Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha Program Magister Manajemen, 2024)
The objectives of this study are: (1) to examine the antecedents of brand love derived from the hedonic value of a product/service, consumer emotions, and brand attachment, and (2) to explore the role of consumer emotions, and brand attachment in strengthening the relationship between hedonic values and brand love. 155 respondents were collected in the current study using the purposive sampling method. The sample criteria in this study are consumers who consume regularly. By using the Smart-PLS module, the test requirements are met both validity, reliability, AVE, and Fornell-Lecker. The results of hypothesis testing show that hedonic value, consumer emotions, and brand attachment influence consumers' love for brands. Further, the current study also found that consumer emotion and brand attachment mediate the relationship between hedonic values and brand love. Therefore, business entities need to consider those constructs to build and maintain relationships between consumers and brands.